MASSIVE THROMBOUS IN THE PRACTICE OF AN OBSTETRICIAN-GYNECOLOGIST (CLINICAL CASE) - Шибельгут, Нонна Марковна; Иванникова, Алена Васильевна; Гришкевич, Елена Валентиновна; Орлова, Елена Николаевна; Власенко, Наталья Фахритдиновна; Демяшкин, Никита Сергеевич; Рудаева, Елена Владимировна; Елгина, Светлана Ивановна; Мозес, Вадим Гельевич; Мозес, Кира Борисовна; Большанина, Елизавета Евгеньевна (Mother and Baby in Kuzbass, 2025)
This article presents a clinical case of bilateral pulmonary artery thromboembolism (PATE) with a low risk score according to the PESI scale (33 points) in a pregnant patient. The case is notable for the unclear duration of PATE, which occurred against the background of proximal thrombosis of the right renal vein and the infrarenal part of the inferior vena cava. The article provides a detailed description of the diagnostic challenges associated with the nonspecific symptoms in pregnant patients and the limitations of imaging techniques. The article discusses the strategy of anticoagulant therapy, the choice of drugs (with a focus on low-molecular-weight heparins), and the management of pregnancy, childbirth, and the postpartum period in patients with massive venous thrombosis.This case highlights the need for high vigilance regarding venous thromboembolic complications in pregnant women, even in the absence of classic high-risk factors.
Keywords: pulmonary embolism; pregnancy; renal vein thrombosis; inferior vena cava thrombosis; anticoagulant therapy